THE ROLE OF QUALITY ADOPTNION IN GROWTH AND MANAGEMENT OF SMALL & MEDIUM ENTERPRISES IN KENYA - Wanjau, Kenneth Lawrence; Gakure, Rosylene W.; Magutu, Peterson Obara; Kahiri, James (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿In today’s business environment, small and medium enterprises (SMEs) cannot afford to ignore the strategic implications of quality for its competitive position. Research shows that most SMEs lose between 5%-15% of sales revenue as a result of the lack of attention to quality. Of the limited research available, it appears that SMEs has been very slow to implement formal quality models, and where they have, the outcomes are inconclusive. The purpose of this study was to investigate the role of quality in growth of SMEs in Kenya. The study focused on manufacturing SMEs that are based in Nairobi and its environs. The study adopted an exploratory approach using a descriptive survey. Stratified random sampling was used and each stratum represented a sub-sector. The data collection instruments were issued to all the 123 firms identified. The response rate was 100%. Statistical analyses were conducted using statistical package for social scientists (SPSS) to calculate descriptive statistics, reliability analysis, factor analysis, t-test, F-test and regression. Results showed that; majority (72%) of the manufacturing SMEs had adopted quality or are implementing quality initiatives; forty five (45%) percent of the SMEs adopting quality are in the agro-based sub sector. Overall, the SMEs level of quality initiative's implementation is below average (mean = 3.49). The results are indicative of the reluctance of SMEs to adopt quality initiatives. The overall results indicated that entrepreneurial management (EM), marketing orientation (MO) and capacity enhancement of employees had a significant linear relationship with quality. The results support the notion that SMEs committed to the adoption of quality do obtain results. The study recommends that SMEs must know what quality management is and what comprises quality management if they are to implement them in their firms.